Can teeage athletes light up in a high competitive sport context without burning out? - Guillet, E.; Gautheur, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Introduction: Female athletes have reported higher levels of competitive state anxiety and train anxiety (Mellalieu, Hanton & Fletcher, 2006) and it has been suggested that they are more susceptible to burnout than their male counterparts (Abrahamson, 1997). Gender differences seem an important psychological parameter as they are likely to influence the quality of the sport experience of high level athletes. The purpose of the current study was to examine whether differences in the anxiety and self-confidence of female and male athletes influence the quality of their sport experience. Based on previous research findings it was hypothesized that female athletes would report higher anxiety and lower self-confidence than male athletes and consequently would also experience lower vitality and higher burnout symptoms. Method: A sample of 790 French handball players (418 males and 372 females) participated in this study. They trained an average of 11.29 hours a week (SD = 3.6). Their average age was 15.82 years (SD = .97). These athletes completed a questionnaire in April 2007 (T1), November 2007 (T2) and April 2008 (T3), during which we measured: (a) anxiety and self-confidence (EEAC; Cury, Sarrazin, Pérès & Famose, 1999), (b) subjective vitality (SSV; Ryan & Frederick, 1997), and (c) athlete burnout (ABQ; Raedeke & Smith, 2001). Results: One-way MANOVAs and post hoc tests Newman Keuls were conducted to examine the differences between boys and girls on (1) anxiety, self-confidence, and vitality; and (2) on the three dimensions of burnout. Findings indicated that (1) females had higher scores of cognitive anxiety and lower scores of self confidence and vitality at T1 (Wilks` λ = .90, F (4, 451) = 11.71, p < .001), at T2 (Wilks` λ = .87, F (4, 460) = 17.41, p < .001) and at T3 (Wilks` λ = .85, F (4, 361) = 15.01, p < .001). Females also had higher scores of somatic anxiety at T1 (Wilks` λ = .90, F (4, 451) = 11.71, p < .001). (2) Males had higher scores of exhaustion at T1 (Wilks` λ = .98, F (3, 451) = 3.71, p < .05). Females had higher scores of reduced accomplishment at T2 (Wilks` λ = .96, F (3, 460) = 6.76, p < .001) and at T3 (Wilks` λ = .94, F (3, 361) = 7.27, p < .001). Discussion: Based on the current findings, young elite female handball players felt more anxious and reported lower accomplishment, while males were more self-confident. However, male athletes reported higher physical and emotional exhaustion in April 2007. Current findings can`t allow us to affirm that females experience higher levels of burnout in a high competitive context. Further investigations are needed.